EFFECT OF WORK EXPERIENCE AND WORK ACHIEVEMENT ON EMPLOYEE SATISFACTION AT PT. VIRAJAYA RIAU PUTRA - Alisya Alisya; Zamhir Basem; Henrizal Henrizal (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine work experience and work performance On the job satisfaction of the employees of PT.Virajaya riauputra, the analysis used in this study is multiple linear analysis. The population in this research is all 60 employees at pt. Virajaya riauputra, This sampling technique is called the census technique. Data collection techniques used are observation methods, questionnaires and research files. Hypothesis testing was carried out with the F test and t test. Based on the results of the study, it can be concluded that simultaneously work experience and work performance on employee job satisfaction, while the partial test of work experience and work performance on employee job satisfaction, the close relationship between the independent variables and the dependent variable. which is very strong with the contribution of the independent variable to the dependent variable of 63.9%. The results of this analysis indicate that work experience and work performance have a significant and partial effect on job satisfaction of Pt. Virajaya riauputra.